1967
DOI: 10.1128/am.15.6.1371-1375.1967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwaves on Escherichia coli and Bacillus subtilis

Abstract: Suspensions of Escherichia coli and Bacillus subtilis spores were exposed to conventional thermal and microwave energy at 2,450 MHz. The degrees of inactivation by the different energy sources were compared quantitatively. During the transient heating period by microwave energy, approximately a 6 log cycle reduction in viability was encountered for E. coli . This reduction was nearly identical to what is expected for the same time-temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Woo et al 46 reported that the viable counts of bacteria B. subilis or Escherichia coli were reduced dramatically in the buffer solution when the microwave heating temperature exceeded 60 C. Stout et al 47 measured the thermal exposure time required to produce the fungicidal effects of Legionellaceae in the liquid broth at 60 C, 70 C and 80 C; these were 1.3 min to 10.6 min, 0.7 min to 2.6 min and 0.3 min to 0.7 min, respectively. Goldblith and Wang 40 showed that microwave could cause no destruction of E. coli in the buffer when held below 51 C. In this study, the germicidal effect on the three strains of fungi and bacteria was demonstrated to occur at a liquid temperature above 60 C. Therefore, the minimum temperature for thermal disinfection would be above 60 C for applications to evaporative humidifiers to be used in office buildings, except for the microorganisms that are resistant to heat. The effectiveness of microwave disinfection for evaporative humidifiers in the living place of susceptible people, like hospitals and facilities with elders or children, could be enhanced more efficiently by increasing the temperature above 70 C or 80 C.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Woo et al 46 reported that the viable counts of bacteria B. subilis or Escherichia coli were reduced dramatically in the buffer solution when the microwave heating temperature exceeded 60 C. Stout et al 47 measured the thermal exposure time required to produce the fungicidal effects of Legionellaceae in the liquid broth at 60 C, 70 C and 80 C; these were 1.3 min to 10.6 min, 0.7 min to 2.6 min and 0.3 min to 0.7 min, respectively. Goldblith and Wang 40 showed that microwave could cause no destruction of E. coli in the buffer when held below 51 C. In this study, the germicidal effect on the three strains of fungi and bacteria was demonstrated to occur at a liquid temperature above 60 C. Therefore, the minimum temperature for thermal disinfection would be above 60 C for applications to evaporative humidifiers to be used in office buildings, except for the microorganisms that are resistant to heat. The effectiveness of microwave disinfection for evaporative humidifiers in the living place of susceptible people, like hospitals and facilities with elders or children, could be enhanced more efficiently by increasing the temperature above 70 C or 80 C.…”
Section: Discussionmentioning
confidence: 69%
“…38 Many researchers had reported that microwave disinfection would occur as a result of thermal effects by heating dielectric materials. 32,39,40,41 Thus, some researchers had reported that the threshold energy of ionization for water and DNA components of microorganisms is 4-5 eV 42,43 and microwaves would be unable to damage DNA components of microorganisms, because the microwave energy would be too low at 1.02 Â 10 -5 eV.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial deactivation using microwave irradiation showed both thermal and non-thermal effects. Goldblith and Wang [ 7 ] compared the deactivation of Escherichia coli and Bacillus subtilis spores using microwave irradiation versus conventional radiant heating. They suggested that the deactivation of these bacteria resulted from the dielectric heating and did not maintain any secondary effect from the microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…T and P are the temperature and power dissipated per unit volume by the EM field in the respective material. In case of nonconductive and nonmagnetic system, the EM power dissipation is due to the dielectric loss which can be describes by [ 37 ] P=12trueE.trueDttrueD.trueEt…”
Section: Introductionmentioning
confidence: 99%